(untitled) (Journal of Parents and Teachers, 2026)
On this occasion, it is the children who have been given this space to pose the questions they wish to share. As the author points out, his answers are merely pointers towards the answer, which must be personal and unique to each individual. Thus, this article contains questions from a number of children—all of them very profound—along with the author’s suggestions, which are intended to mark the beginning of an ‘unfinished dialogue’ fuelled by the children’s curiosity.